Flambards divided - Peyton, K. M. (New York : Philomel Books, 1982)
Widowed Christine marries hard-working Dick, hoping to make Flambards a thriving farm again, but their life is complicated when her cousin Mark returns from the war gravely wounded.
Sequel to : Flambards in summer.
Keywords: Country life -- England -- Fiction; England -- Fiction